Translation state - Leckie, Ann (Orbit, 2023)
"When Enae's grandmaman passes away, Enae inherits something entirely unexpected: a diplomatic assignment to track down a fugitive who has been missing for over 200 years. No one actually expects Enae to succeed; it's an empty assignment meant to keep hir occupied. But Enae has never had a true purpose-no one ever expected hir to do more than care for grandmaman-so sie is determined to accomplish this task to the best of her ability. Reet knows nothing about his biological family. He loves his adoptive parents, but has always secretly yearned to understand his identity, the roots that would explain why he seems to operate just a bit differently. After all, no one else hungers to study the world by ripping it apart, by slicing into those around them in order to make sense of things. So when a political group approaches him with the claim that he has ties to a genetically mysterious, long-deceased family, Reet is only too eager to believe them. Qven was created to be a Presgr translator. The pride of their Clade, they always had a clear path before them: learn human ways, and eventually, make a match and serve as an intermediary between the dangerous alien Presgr and the human worlds. The realization that they might want something different isn't "optimal behavior". It's the type of behavior that will have you eliminated. But Qven rebels anyway, determined to find a way to belong on their own terms. As a Conclave of the various species approaches-and the long-standing treaty between the humans and the Presgr is on the line-the paths of all three will collide in a chain of events that will have ripple effects across galaxies"--